The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1063/1.121470
|View full text |Cite
|
Sign up to set email alerts
|

Phases of cobalt-iron ternary disilicides

Abstract: Cobalt–iron transition-metal disilicides were investigated by Mössbauer effect and x-ray diffraction in order to determine the concentration range of their homogeneous and separate phase formation. Except at low Co or Fe concentrations, Co and Fe formed separate CoSi2 and FeSi2 phases. Up to 10 at % Co was found soluble in β-FeSi2; Fe dissolved in CoSi2 below 1.5 at % and was positioned at two different sites of cubic symmetry. The results obtained for the phase formation in thin layers of epitaxial CoSi2 on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…14 For the bulk samples line 1 was attributed to substitutional Fe atoms, line 3 to Fe atoms positioned in the vacant cube of Si in the CoSi 2 lattice. 5 The close CS1 and CS3 values of the implanted and bulk samples indicate the same or very similar atomic arrangements in the two samples. This is also supported by the annealing behavior of the implanted samples, e.g., the intensity of line 3 increased at a high temperature indicating that this position is more stable for Fe, similarly, this behavior is similar to that of the bulk and 57 Fe implanted CoSi 2 samples.…”
Section: Metastable Phases Of Cobalt-ironsilicide Formed By Sequentiamentioning
confidence: 88%
See 2 more Smart Citations
“…14 For the bulk samples line 1 was attributed to substitutional Fe atoms, line 3 to Fe atoms positioned in the vacant cube of Si in the CoSi 2 lattice. 5 The close CS1 and CS3 values of the implanted and bulk samples indicate the same or very similar atomic arrangements in the two samples. This is also supported by the annealing behavior of the implanted samples, e.g., the intensity of line 3 increased at a high temperature indicating that this position is more stable for Fe, similarly, this behavior is similar to that of the bulk and 57 Fe implanted CoSi 2 samples.…”
Section: Metastable Phases Of Cobalt-ironsilicide Formed By Sequentiamentioning
confidence: 88%
“…Because of their different structures, cobalt and iron do not form a stable single phase in a broad range of concentrations. 5 In contrast to the case of the stable phases, it was shown that by using ion implantation, cobalt and iron can form a metastable homogeneous single phase of fluorite structure in broad concentration ranges. [6][7][8] Even iron might form metastable disilicide (␥-FeSi 2 ͒ of fluorite structure if one applies ion beam induced epitaxial crystallization on iron implanted in Si.…”
Section: Metastable Phases Of Cobalt-ironsilicide Formed By Sequentiamentioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, because of the different crystal structures thermodynamically stable phases with Fe do not form in a broad concentration range. 9 After implanting Co and Ni in Si at 623 K, at relatively low doses, it was observed that segregated crystalline CoSi 2 and NiSi 2 phases in fluorite structure formed in the target lattice. 2,3,6 After subsequently implanting Fe into this system, a mixed Fe-containing phase forms which still has a structure of cubic symmetry.…”
Section: Introductionmentioning
confidence: 98%
“…1 In particular, ion-beam synthesis of ternary iron silicides (Me x Fe 1Ϫx Si 2 ) has been studied by several groups. [2][3][4][5][6][7][8][9][10] The interest in the latter system is triggered by its potential use in advanced silicon based ͑opto-͒electronic devices. [11][12][13][14][15][16] Ternary silicides have been by far less studied than their binary counterparts despite the fact that they might be beneficial to decrease the formation temperature of disilicides.…”
Section: Introductionmentioning
confidence: 99%